The Effect of Postpartum Exercise on Decreasing Uterine Fundal Height (TFU) in Postpartum Mothers at the Long Iram Health Center - Aisyah Ayu Mentari; Edi Sukamto; Siti Raihanah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the effect of postpartum exercise on reducing uterine fundal height (TFU) in postpartum women at the Long Iram Health Center. This type of research uses the pre-experiment one group pretest-posttest design method. The population in this study were all postpartum mothers who gave birth at the Long Iram Health Center in June-July 2022, totaling 10 people. The sampling technique used is total sampling. Data analysis technique using the Wilcoxon test Based on the research that has been conducted and the data obtained, it can be concluded that there is an effect of postpartum exercise on a decrease in TFU in postpartum women at the Long Iram Health Center in 2022 with a p-value = 0.000 (<0.05).